Systematic Literature Review (Slr): the Influence of Quizzz Learning Media on Students' Learning Outcomes in Elementary School - Helis Ira Setiawati; Latif fatul Tamara; Uswatun Ni’mah; Putri Tiara Hidriana; Fina Fakhriyah; Erik Aditia Ismaya (MultiTech Publisher, 2024)
This study aims to conduct a literature review related to the influence of quizizz learning media on student learning outcomes in elementary schools. in this study using the SLR (Systematic Literature Review) method. Data collection techniques are carried out by finding sources of articles that have similar research in this study. The articles used in this research are 12 national journal articles obtained from the Google Solar database using the Harzing's Publish Or Perish application. The results of the study show that quiziz is a fun learning medium, because in the quiziz application an educator can add interesting features and can arouse students' curiosity. It can be concluded that the use of Quizziz as a learning medium in elementary schools is very effective in improving student learning outcomes.